Molecular dynamics investigation on the inhibition of MDM2-p53 interaction by polyphenols - Verma S.; Singh A.; Mishra A. (My University, 2025)
Inhibition of the MDM2-p53 interaction has become a new therapeutic strategy to activate wild type p53 in tumors. Quercetin and taxifolin bind to p53 binding hydrophobic groove of MDM2, and alter the conformation of groove as evidenced by 65 ns molecular dynamics simulation. Quercetin showed hydrogen bonding with Gly 16, Ser 17, Phe 55 and Val 93 along with π-π interaction with His96 and π-σ with Phe 55. Taxifolin also showed similar interactions except π-σ interaction with Phe 55. Further, we found that binding of ligands lead to the dissociation of MDM2-p53 complex. These ligands form stable hydrophobic interactions with MDM2 which led to complete disruption of MDM2-p53 hydrophobic interactions and dissociation of p53 from the complex. It was found that the π-π stacking between Tyr 51 of MDM2 and ligands is the critical event in MDM2-p53 dissociation. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.